Flow cytometry evaluation of infection-related biomarkers in febrile subjects in the emergency department - Bourgoin, Pénélope; Lediagon, Guillaume; Arnoux, Isabelle; Bernot, Denis; Morange, Pierre-Emmanuel; Michelet, Pierre; Malergue, Fabrice; Markarian, Thibaut (Future microbiology, 2020)
In an Emergency Department (ED), the etiological identification of infected subjects is essential. 13 infection-related biomarkers were assessed using a new flow cytometry procedure. If subjects presented with febrile symptoms at the ED, 13 biomarkers’ levels, including CD64 on neutrophils (nCD64) and CD169 on monocytes (mCD169), were tested and compared with clinical records. Among 50 subjects, 78% had bacterial infections and 8% had viral infections. nCD64 showed 82% sensitivity and 91% specificity for identifying subjects with bacterial infections. mCD169, HLA-ABC ratio and HLA-DR on monocytes had high values in subjects with viral infections. Biomarkers showed promising performances to improve the ED's infectious stratification.